EVALUASI SISTEM INFORMASI SUMBER DAYA MANUSIA PADA BIDANG USAHA JASA - Noerlina, Noerlina (Bina Nusantara University, 2008)
Human Resource Information System has become a reference to get assurances from the availability of appropriate manpower to occupy a position and the right job and right time for organizations to realize the goals and objectives of the company. Therefore, the company will be in desperate need of a performance of high quality human resources. The evaluation of Human Resource Information System is needed to improve the performance of the required human resources activities, including internal within the company such as recruiting, selecting, training for new employees.Keywords: evaluation, Information System, Human Resource